Clostridioides difficile Prevalence in the United States: National Inpatient Sample, 2016 to 2018. (30th July 2021) - Petersen, Molly R; Cosgrove, Sara E; Klein, Eili Y; Zhu, Xianming; Quinn, Thomas C; Patel, Eshan U; Grabowski, M Kate; Tobian, Aaron A R
Abstract: Data from the National Inpatient Sample indicate that Clostridioides difficile prevalence decreased from 10.1 (95% confidence interval [CI] = 9.9–10.3) to 8.6 (95% CI = 8.5–8.8) per 1000 hospital discharges between 2016 and 2018, after accounting for age, sex, and race. There was heterogeneity in the prevalence and decrease in prevalence by geographic region in the United States.